2022
DOI: 10.1021/acsanm.2c04019
|View full text |Cite
|
Sign up to set email alerts
|

Hollow Nanospheres of Red Phosphorus for Fireproof Flexible Sensors Fabricated via 3D Printing

Abstract: High-power and high-temperature applications have brought increased demand for electrical sensing systems; however, conventional sensors have often been designed without consideration for stability in extreme environments (e.g., fire). Red phosphorus (RP) is a highly effective commercial flame retardant; however, its sensitive properties and large size predispose it to spontaneous combustion during shearing and make it difficult to combine with direct inkjet writing technology carrying micron-sized pinholes to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The acceptable mechanical property is mainly ascribed to the better interfacial compatibility between the filler and the polyurea matrix. The open structure of OZCs enhances the interfacial interaction between the filler and the polymer chains, and OZCs and Co 3 O 4 cooperate to play the enhancement mechanism of dimension dislocation as well. , Notably, the blended polyurea composites with nano-Co 3 O 4 showed the worst mechanical properties (Table S9). On the one hand, this is due to the complete removal of ligands during the evolution of ZIF-67 into nano-Co 3 O 4 , while the ligands facilitate the enhancement of the compatibility between the filler and the polyurea matrix.…”
Section: Resultsmentioning
confidence: 99%
“…The acceptable mechanical property is mainly ascribed to the better interfacial compatibility between the filler and the polyurea matrix. The open structure of OZCs enhances the interfacial interaction between the filler and the polymer chains, and OZCs and Co 3 O 4 cooperate to play the enhancement mechanism of dimension dislocation as well. , Notably, the blended polyurea composites with nano-Co 3 O 4 showed the worst mechanical properties (Table S9). On the one hand, this is due to the complete removal of ligands during the evolution of ZIF-67 into nano-Co 3 O 4 , while the ligands facilitate the enhancement of the compatibility between the filler and the polyurea matrix.…”
Section: Resultsmentioning
confidence: 99%
“…3l and m). 51,52 This dimensional mismatch structure can effectively avoid the early fracture of the EP composites due to the excessive stress caused by the local filler agglomeration during mechanical loading. 53,54 3 Function of cleft MOFs and the application as FRs…”
Section: Industrial Chemistry and Materialsmentioning
confidence: 99%
“…26 Amorphous red-P is the most versatile phosphorus allotrope. Because of its low cost, environmental friendliness, availability, and stability, it finds applications in various fields such as flame retardants, 27 energy harvesting, 23,28 ion storage, 29 and pollution sensing. 30,31 During the synthesis of red-P, Hittorf and Thurn et al observed the formation of plate-like and fiber bundles of phosphorus crystals, namely, violet phosphorus (violet-P) and fibrous phosphorus (fibrous-P), respectively.…”
Section: Introductionmentioning
confidence: 99%